Comparative anatomy of the arm muscles of the Japanese monkey (Macaca fuscata) with some comments on locomotor mechanics and behavior. Issue 4 (14th June 2016) - Aversi‐Ferreira, Tales Alexandre; Aversi‐Ferreira, Roqueline A.G.M.F.; Bretas, Rafael Vieira; Nishimaru, Hiroshi; Nishijo, Hisao
Abstract: Background: The anatomical literature on the genus Macaca has focused mainly on the rhesus monkey. However, some aspects in the positional behaviors of the Japanese monkey may be different from those in rhesus monkey, suggesting that the anatomical details of these species are divergent. Methods: Four thoracic limbs of Macaca fuscata adults were dissected. Results: The arm muscles in Japanese macaques are more similar to rhesus monkeys and Papio ; these characteristics are closer to those of bearded capuchins than apes, indicating more proximity of this genus to New World primates. Conclusions: The anatomical features observed favor quadrupedal locomotor behaviors on the ground and in arboreal environments. Japanese monkeys, rhesus monkeys, and bearded capuchins, which share more primitive characteristics in their arm muscles, present features that favor both arboreal and quadrupedal locomotor behaviors, whereas apes, mainly Pan and Gorilla, which spend more time on the ground, present more quadrupedal specializations.